YAP in MAPK pathway targeted therapy resistance - Keith T. Flaherty; Jennifer A. Wargo; Trever G. Bivona (2015)
Within the past several years, there have been major advances in cancer treatment through the use of molecularly targeted therapy, though resistance to therapy remains a significant issue. The clin...